2020
DOI: 10.1002/oby.22923
|View full text |Cite
|
Sign up to set email alerts
|

Obesity is Associated with Worse Outcomes in COVID‐19: Analysis of Early Data from New York City

Abstract: Objective The 2019 novel coronavirus disease (COVID‐19) has triggered a rapidly expanding global pandemic in which patients exhibit a wide spectrum of disease severity. Given the high prevalence of obesity in the United States, we hypothesized that the presence of obesity may play a role in the clinical course of patients with COVID‐19. Methods This is a retrospective review of adult patients admitted with confirmed severe acute respiratory syndrome coronavirus 2. Demographics, clinical characteristics, labora… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
192
4
17

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 195 publications
(223 citation statements)
references
References 33 publications
10
192
4
17
Order By: Relevance
“…A few studies showed that individuals with obesity may decrease in‐hospital mortality 31,75,87,89 . Some studies showed that obesity may insignificantly decrease 41,47,81,90 or increase 55,67,68,84,91–96 the odds of death among individuals with obesity. The majority of studies showed that obesity significantly increased the odds of death among COVID‐19 patients with obesity.…”
Section: Epidemiological Relationships: Individuals With Overweight Amentioning
confidence: 99%
“…A few studies showed that individuals with obesity may decrease in‐hospital mortality 31,75,87,89 . Some studies showed that obesity may insignificantly decrease 41,47,81,90 or increase 55,67,68,84,91–96 the odds of death among individuals with obesity. The majority of studies showed that obesity significantly increased the odds of death among COVID‐19 patients with obesity.…”
Section: Epidemiological Relationships: Individuals With Overweight Amentioning
confidence: 99%
“…The MUST is assigned a point in the BMI domain for people with a BMI less than 20 kg/m 2 . Several studies have reported a high prevalence of overweight and obesity among patients with COVID-19, with few older adults with COVID-19 having low weight [ 56 , 57 ]. In a study including 37 patients with a mean age over 60 years, 23 were overweight (BMI > 24.9 kg/m 2 ), 13 were adequate weight (BMI between 18.5 and 24.9 kg/m 2 ), and only 1 was underweight (BMI < 18.5 kg/m 2 ) [ 57 ].…”
Section: Discussionmentioning
confidence: 99%
“…Aging, obesity, uncompensated type 2 diabetes mellitus (T2DM), hypertension, male sex, and presence of male androgenetic alopecia (AGA) have been detected as risk factors for COVID-19 complications (1)(2)(3)(4)(5)(6).…”
Section: Covid-19 Is a Multi-systemic Infection Caused By The Severe mentioning
confidence: 99%